2016
DOI: 10.1038/s41598-016-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Controllable and fast quantum-information transfer between distant nodes in two-dimensional networks

Abstract: We construct shortcuts to adiabatic passage to achieve controllable and fast quantum-information transfer (QIT) between arbitrary two distant nodes in a two-dimensional (2D) quantum network. Through suitable designing of time-dependent Rabi frequencies, we show that perfect QIT between arbitrary two distant nodes can be rapidly achieved. Numerical simulations demonstrate that the proposal is robust to the decoherence caused by atomic spontaneous emission and cavity photon leakage. Additionally, the proposed sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…These results are included in the Supplementary Information (Supplementary Fig. 4 ) and show a ratio of the intensities of the peaks associated with the A 1 g and A 2 g modes 31 , 55 , 57 61 of ~0.4, consistent with an oxide-free surface 31 , 57 ; this value is unchanged for the CA.M-terminated sample exposed to the atmosphere for a month consistent with the passivating effect discussed above.…”
Section: Resultssupporting
confidence: 54%
“…These results are included in the Supplementary Information (Supplementary Fig. 4 ) and show a ratio of the intensities of the peaks associated with the A 1 g and A 2 g modes 31 , 55 , 57 61 of ~0.4, consistent with an oxide-free surface 31 , 57 ; this value is unchanged for the CA.M-terminated sample exposed to the atmosphere for a month consistent with the passivating effect discussed above.…”
Section: Resultssupporting
confidence: 54%
“…In the present study, patients with OXTC were older (57.69 years old), compared to patients with PTC and FTC. Many studies have indicated that age plays a unique prognostic role in thyroid cancer [ 18 , 20 , 21 ], and the present study confirmed that age was an independent risk factor for both cancer-specific and all-cause mortality. Furthermore, PSM for age, race, and sex confirmed that OXTC was associated with a better prognosis, compared to PTC and FTC.…”
Section: Discussionsupporting
confidence: 86%
“…Subsequently, the authors concluded that GPR84 does not modulate microglial responses in the spinal dorsal horn, because GPR84 deficiency caused no alterations in microglial number and activation determined by ionized calcium-binding adapter molecule 1 and p-p38 immunostaining, respectively. Nonetheless, microglia responded to nerve injury with prominent up-regulation of GPR84 mRNA in the neuropathic pain model [ 13 ], as well as our motor nerve injury model [ 3 ], in which circulating macrophages do not contribute to the microglial pool [ 14 16 ], and thereby conflicts with the conclusion that there is no functional consequence of GPR84 deficiency in microglia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%